Readings in the Canon of Scripture - Jasper, D. author. aut Link
XX, 156 p.
Keywords: Beginning with the insights of the 'canonical criticism' of Brevard Childs and James Sanders, this book explores the canon of the Bible through readings in literature, art and cinema. It places the Bible within the concerns of contemporary feminist thought, postmodern anxiety and modern apocalyptic. It returns us to a sense of the centrality of the Biblical canon in the present of critical thought and popular culture, expanding the notion of 'reading' to picture and film.